计算(m+2n/n-m)-(n/m-n)+(2m/n-m)要过程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 01:33:19
计算(m+2n/n-m)-(n/m-n)+(2m/n-m)要过程计算(m+2n/n-m)-(n/m-n)+(2m/n-m)要过程计算(m+2n/n-m)-(n/m-n)+(2m/n-m)要过程(m-n
计算(m+2n/n-m)-(n/m-n)+(2m/n-m)要过程
计算(m+2n/n-m)-(n/m-n)+(2m/n-m)要过程
计算(m+2n/n-m)-(n/m-n)+(2m/n-m)要过程
(m-n)^3+(n-m)m^2
=(m-n)^3-(m-n)m^2
=(m-n)[(m-n)^2-m^2]
=(m-n)(m-n+m)(m-n-m)
=-n(m-n)(2m-n)
=-n(2m^2-3mn+n^2)
=-2m^2n+3mn^2-n^3
原式=(m+2n)/(n-m)+n/(n-m)+2m/(n-m)
=(m+2n+n+2m)/(n-m)
=(3m+3n)/(n-m)
(m+2n)/(n-m)-n/(m-n)+2m/(n-m)
=(m+2n)/(n-m)+n/(n-m)+2m/(n-m)
=[(m+2n)+n+2m]/(n-m)
=(3m+3n)/(n-m)
=[3(m+n)]/(n-m)
计算M-N+(2N的平方/M+N)
计算(3-m+n)*(3+m-n)-(2-m+n)*(2+m-n)
计算:(m+n)²(m-n)²-(2m+n)²(2m-n)²
计算:(-m-n)(m+n)
计算(m+2n/n-m)-(n/m-n)+(2m/n-m)要过程
计算(m-n)(n-m)
计算m+2n/n-m+n/m-n-2n/n-m
(m-n)m立方;+2n(n-m)平方
计算 (m-2n)^2(m+2n)^2
计算:(m+2n)(m-3n)
计算m+2n/n-m+n/m-n-2m/n-m
计算2m-n/n-m+m/m-n+n/n-m
计算:2m-n/n-m+m/m-n+n/n-m
计算(m+n)^3-(n+m)(m-n)^2
计算(m+2n)-(m-2n)?
计算m-n^2+m-n^2
计算(m-n)^2*(-m+n)^2
计算-(m-n)^2-(m+n)^2